(untitled) (Research, Society and Development, 2020)
The objective of the work was to evaluate production and decomposition of biomass, accumulation and cycling of nutrients by single, intercropped or polyculture cover crops. The study was conducted in two experimental areas, at the Cedeteg Campus, characterized as a low fertility area, and a school farm, characterized as a high fertility area, belonging to UNICENTRO in Guarapuava, PR. The design used was randomized blocks, with 3 treatments and 4 repetitions, being the treatments: single cultivation, intercropping and polyculture of winter cover plants. Biomass production, accumulation of nutrients in biomass (N, P, K, Ca and Mg), C / N ratio, decomposition, and nutrient release were evaluated. For low fertility soils: single cultivation showed higher biomass production and concentration of P and K; for C/N ratio there was no difference; single and polyculture cultivation showed higher residual biomass at 120 days after management; single cultivation had a shorter half life time for most nutrients. For soils with high fertility: consortium and polycultures showed higher biomass production and Mg accumulation; polycultivation presented a greater accumulated amount of N, the consortium accumulated a greater amount of Ca; single cultivation presented a lower C/N ratio and a half life span for nutrients. Single cultivation has an aptitude for nutrient cycling and an increase in biomass in low fertility soils. For highly fertile soils, the consortium and polyculture are options for nutrient cycling and high biomass production.